FRI0025 Predicting Rheumatoid Arthritis by Measuring Survivin in Unselected Samples – Epidemiological Study Within Two University Cities of Sweden. (9th June 2015) - Turkkila, M.; Pullerits, R.; Schiller, C.; Eriksson, C.; Erlandsson, M.; Rantapää-Dahlqvist, S.; Bokarewa, M.
Abstract : Background: Survivin is a sensitive biomarker predicting development of rheumatoid arthritis (RA) several years ahead of clinical symptoms (1). In early RA, more than 50% of the patients have high serum levels of survivin (2), which recognises the patients with poor treatment responses and progressive joint damage (3). Objectives: In this study we evaluated predictive potential and specificity of serum survivin for early recognition of RA. Methods: All serum samples of individuals >18 years of age referred during the period of 12 months to the Laboratories of Clinical Immunology at the University Hospitals of Gothenburg and Umeå in Sweden were enrolled in the analysis of survivin, rheumatoid factor (RF) and/or anti-citrullinated peptide (ACPA) antibodies. Serum levels of survivin were measured using a sandwich ELISA, and the levels >0.45 ng/ml were considered positive. Medical records of the individuals positive for survivin and RF/ACPA antibodies were reviewed by independent experts to identify cases with newly-diagnosed RA, established RA, and unexplained arthralgia. Results: The total of 8868 (5422 Gothenburg, 3446 Umeå) adult individuals were analysed and the prevalence of survivin-positive samples was 11.2% and 14.7%, respectively. Among 921 survivin-positive samples, 46% were also positive for RF and/or ACPA vs 10% of survivin-negative, and indicated that survivin-positive individuals had increased estimated risk for being also RF/ACPA positive (RR 4.44[4.01-4.92], p<10 -7 ). Survivin levels were significantly higher in patients with combined positivity of survivin and RF/ACPA (p<0.001). Established RA cases were identified equally often among survivin-positive (15.7%) and in survivin-negative-RF/ACPA-positive (19%) cohorts. Newly-diagnosed RA cases were more prevalent within survivin-positive vs survivin-negative-RF/ACPA-positive cohorts (OR 1.84, p=0.064). The difference between survivin-positive vs survivin-negative-RF/ACPA-positive cohorts was even higher for the arthralgia cases (OR 3.42, p<10 -7 ). This difference between the cohorts was due to the increasing prevalence of newly-diagnosed RA compared to arthralgia cases in survivin-negative-RF/ACPA-positive cohort (15.3% vs 7.2%, p=0.0004), while this prevalence did not change in surviving-positive cohort (27% vs 21%, respectively). Conclusions: In the unselected serum samples, high levels of survivin were associated with RF and/or ACPA antibodies. Cases with arthralgia and newly-diagnosed RA were accumulated within the Survivin-positive samples and suggest a predictive potential of survivin early in the disease course. References: Bokarewa M et al., Arthritis Res Ther 2014;16(1):R45 Svensson B et al., Ann Med 2010;42:45-54 Svensson B et al., Arthritis Res Ther 2014;16(1):R12 Disclosure of Interest: None declared